pengaruh penambahan air perasan daun pepaya(Carrica papaya L) dalam air minum terhadap performans ayam broiler - andy andytriwibowo; Novi Eka Wati; Miki Suhadi (Wahana Peternakan, 2021)
ABSTRACT Herbal plants can be used as feed additive, on of which is the papaya plant (Carrica papaya L). The reseach was conducted on 11-27 September 2020 at street Wolter Monginsidi alley Nuri number 55, Teluk Betung North District, Bandar Lampung. This study aims to determine the effect of adding papaya leaf juiceÂ  in drinking water to the performance broiler chickens. The material used was 96 broiler chickens ranging from 5-21 days of age. The method used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatments given was control drinking water without additionalÂ  (P0), control drinking water + 5 ml papaya leaf juice/liter of water (P1), control drinking water + 10 ml papaya leaf juice/liter of water (P2), control drinking water + 15 ml papaya leaf juice/liter of water (P3). The result showed that the addition of papaya leaf juice up to level 1,5% did not have a significant effect on the performance of broiler chickens at weeks 1, 2, and 3. Based on the reseach result it can be concluded that the addition of papaya leaf juce in drinking water up to level 1.5% has not had a significant effect (P>0,05) on performance broiler chicken. Keywords : Broiler Chicken, Papaya Leaf Juice, Drinking Water, Broiler Performance